ETIQUETTE SPEECH OF PRESCHOOLERS AS AN INDICATOR OF COMMUNICATIVE AND SPEECH READINESS FOR STUDYING IN THE CONTEXT OF THE NEW UKRAINIAN SCHOOL - Kuzmenko, Vira; Karabaeva , Irina (PSYCHOLOGICAL JOURNAL, 2023)
This research focuses on the importance of etiquette speech as a key indicator of older preschoolers’ readiness for school life in the new Ukrainian school. While many studies explore various aspects of preschoolers’ readiness for school, inadequate attention has been given to the specifics of mastering etiquette speech by future first graders, the acquisition of effective linguistic units, and the identification of significant situations for etiquette speech development. The urgency of this research is underscored by its vital role in the moral and cultural education of the younger generation and successful adaptation to new socio-cultural priorities and challenges, making it pedagogically significant in the development of the new Ukrainian school. The study introduces novel approaches to the thesaurus, diagnosis, and tools for etiquette speech development in preschoolers. The article outlines key terminological categories, depicting their relationships through a diagram based on the degree of dependence. The essence and content of the key concept, "etiquette speech of preschoolers," are clarified, emphasizing that it primarily manifests respect. The research presents results from an experimental study on the features of etiquette speech development in older preschoolers. A development program is characterized, which is designed based on creating emotionally rich educational situations with specific goals. The program aims to instill etiquette speech skills, transferring knowledge on proper behavior into habitual and comfortable actions, leading to the automatic execution of socially acceptable behaviors. These skills serve as evidence of a certain cultural level of the individual and act as a prerequisite for effective interaction with others. Experimental situations, involving the identification and improvement of etiquette speech skills, the consolidation of etiquette formulas, and enhanced communication between participants, form the basis of the program. The authors demonstrate the effectiveness of the proposed method, showing that, during the formative experiment (through conversation), the children achieved 100% understanding of politeness concepts and knowledge of related words.